COMPASSION FATIGUE IN HEALTHCARE WORK: FROM INVOLVEMENT TO DISTRESS, FROM VULNERABILITY TO PROTECTION - Ana Paula Simão Ponce; Sannara das Graças Freitas de Moraes Alcântara; Werlisson da Silva Felismino; Nahieny Gomes Prudente; Ana Clara Barroso Soares; Kimberly de Sousa Guimarães; Caroline Oliveira Bezerra; Marcelo Rodrigues da Silva (Artefactum - revista de estudos interdisciplinares, 2026)
This article discusses compassion fatigue in healthcare work through a narrative review of the Brazilian literature. It sought to understand how the phenomenon presents itself among healthcare professionals and to analyze factors associated with vulnerability and professional quality of life. The study is justified by the emotional impacts of care, since empathic involvement, exposure to suffering, established bonds, and contact with loss, trauma, and terminal illness may affect workers’ mental health. After applying the inclusion and exclusion criteria, the corpus comprised seven articles published between 2021 and June 2026. The studies were organized into two categories: the first, comprising three articles, addresses manifestations and contexts of strain related to compassion fatigue; the second, comprising four studies, examines factors associated with professional quality of life and resources for continuing to provide care. The material was analyzed using Bardin’s Content Analysis. The results identified sadness, distress, guilt, helplessness, recurring memories, emotional distancing, and difficulty separating professional and personal life among the experiences associated with care-related strain. The intensity of these experiences varies according to personal characteristics, support networks, professional relationships, and living and working conditions. Age, experience, self-compassion, family support, support from the healthcare team, perceived usefulness, and meaning-making were associated with lower vulnerability or with coping with strain. It is concluded that preserving professional quality of life requires the articulation of individual, collective, and institutional resources.